Brownies Pisang Sebagai Pangan Funsional Pencegahan Masalah Gizi Pada Ibu Hamil - Rate, Suherman; Ishak, Syamsopyan; Dewanti, Ritma; Dewi, Apiska Prima (Jurnal Ilmu Kebidanan, 2024)
Background: bananas can be used as an alternative staple food because of their high carbohydrate content. Objective: This research aims to find a formulation for making brownies from banana flour and analyze its acceptability and nutritional content. Methods: This research uses a laboratory experimental method with diversified treatment of banana flour in brownies to produce this most preferred product using a hedonic test, then a proximate analysis test is carried out on each sample compared with the control. The method used was a Completely Randomized Design (CRD) method with three repetitions in testing the nutritional content. Results: there is an effect of nutrition education on nutritional knowledge in female adolescents with p = 0.000. Conclusion: There is a significant difference in treatments F1, F2, F3, and F4 with banana flour substitution. There were real differences in the treatment of F1, F2, F3, and F4 on water content, ash content, protein content, fat content, crude fiber content, and carbohydrate content in brownies with banana flour substituted. The potential for banana flour to become a functional food raw material is very high.